2003
DOI: 10.1046/j.1439-0523.2003.00860.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity in clover species from Sardinia, Italy, using AFLP analysis

Abstract: Two species, Trifolium glomeratum and T. nigrescens, from Sardinia, Italy, were analysed for genetic diversity using amplified fragment length polymorphism (AFLP). Variation between and within populations was compared between the inbreeder, T. glomeratum, and the outbreeder, T. nigrescens. Four AFLP primer combinations resulted in a total of 292 loci, of which 75% were polymorphic in T. glomeratum and 85% in Trifolium nigrescens. Variation was highest between populations in both species, but the difference bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For alfalfa populations, this primer combination produced the highest mean number of polymorphic fragments (29.9) per population, which was considered relatively low compared to the results of other studies in the same or related species according to Dobrzycka et al (2009). In addition, for clover species, this primer combination amplified 52 bands across four studied populations, which was the lowest number among the four primers used (Bennett and Mathews, 2003). In other studies, an average 25.2 markers generated per pairwise combinations (10 primers combinations) with a highest number of 28 markers was sufficient for analyses of genetic structure and diversity in eight populations of Parapiptadenia rigida (De Souza et al, 2013).…”
Section: Molecular Characterizationmentioning
confidence: 61%
See 1 more Smart Citation
“…For alfalfa populations, this primer combination produced the highest mean number of polymorphic fragments (29.9) per population, which was considered relatively low compared to the results of other studies in the same or related species according to Dobrzycka et al (2009). In addition, for clover species, this primer combination amplified 52 bands across four studied populations, which was the lowest number among the four primers used (Bennett and Mathews, 2003). In other studies, an average 25.2 markers generated per pairwise combinations (10 primers combinations) with a highest number of 28 markers was sufficient for analyses of genetic structure and diversity in eight populations of Parapiptadenia rigida (De Souza et al, 2013).…”
Section: Molecular Characterizationmentioning
confidence: 61%
“…Badri et al (2008) used SSRs to characterize Tunisian populations of M. ciliaris and reported that 80.94% of the total diversity occurs at the intra-population level. Similar studies on the genetic diversity of various land plants reported the same results, including Trifolium glomeratum and Trifolium nigrescens (Bennett and Mathews, 2003), Hedysarum coronarium (Marghali et al, 2003), Alfalfa (Medicago sativa L.) (Keivani et al, 2011), perennial ryegrass (Lolium perenne L.), and tall fescue (Festuca arundinacea Schreb.) (Elazreg et al, 2011).…”
Section: Molecular Characterizationmentioning
confidence: 62%
“…Other factors like heterogeneous populations and ecogeographical condition of the place of collection might be responsible for variation among these species. In a study on populations of T. glomeratum and T. nigrescens, Bennett and Mathews (2003) have also concluded that interpopulation variations are contributed by factors like preferred habitat, ecogeographic conditions whereas intrapopulation variation are also caused by growing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, randomamplified polymorphic DNA (RAPD) markers have been applied to species of Trifolium (Bullitta and Hayward, 1996;Kongkiatngam et al, 1996) in order to study the relationships of taxa. Genetic diversity was shown with amplified fragment length polymorphism (AFLP) markers in 2 Trifolium species from Italy (Bennett and Mathews, 2003). Another study was done with 31 Trifolium species using internal transcribed spacer (ITS) markers (Vizintin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%